Improving Writing Skills in English as A Foreign Language: UnderstandingWriting Through Types of Paragraph - Harun Al Rasyid Harun Al Rasyid; Nabila Adinda Wulandari; Naning Triana; Radinda Nasyfa Yolanda (Nalar Global, 2020)
This study aims to provide information and add insight and reference for readers. It discusses parts of paragraphs in an article in order to increase readers’ insight on how different paragraphs are in writing: Descriptive, Narrative, Persuasive and Expository.The method in this article is the literature review method, which is based on theories related to to the topic or idea being discussed taken from accurate journals. With this method, it will be easier for the author to complete this article, and hopefully it makes it easier for readers to understand how to take the information and make it a reference. This study found that while the current findings give extra insights into the perception of reading comprehension via mobile phones, the key analysis findings show that learners favor reading comprehension via mobile phones because of the convenience expedited by the movableness and accessibility of the mobile phones.